HGG-34. A DNA DAMAGE REPAIR SIGNATURE IN PRIMARY AND RECURRENT PEDIATRIC HIGH-GRADE GLIOMAS: PROGNOSTIC AND THERAPEUTIC VALUE. (1st June 2021) - Entz-Werle, Natacha; Poidevin, Laetitia; Nazarov, Petr; Lhermitte, Benoit; Chenard, Marie Pierre; Poch, Olivier; Dontenwill, Monique; Van Dyck, Eric
Abstract: Pediatric high-grade gliomas (pHGGs), including diffuse intrinsic pontine gliomas (DIPGs), despite their low incidence, are the leading cause of mortality in pediatric neuro-oncology. Frequently, pHGGs, harboring mainly histone mutations, are or become resistant to standard therapies like irradiation or chemotherapies. Recent insights showed in adult HGG the predominant role of DNA damage repair (DDR) as a way of prognostic classification. Given the recent evidence that transcription conflicts like in histone-mutated gliomas can induce replication stress and be linked to DDR abnormalities, this study is aiming to establish a DDR signature able to classify specifically pHGGs and to cluster among them poor responders to radiation. Transcriptomic analyses were performed to discriminate seven pHGGs comparatively to a cohort of 10 pilocytic astrocytomas with specific DDR deregulations. The specific transcriptomic signature obtained from this differential gene expression analysis was compared to the aHGG signature already established. To strengthen, refine and finalize the DDR signature able to classify and cluster the pHGGs, we explored both signatures and their common genes in already published transcriptomic analyses of DIPGs and sus-tentorial pHGGs. To check DDR protein expressions correlated to loss of trimethylation as well as histone and TP53 mutations, an immunohistochemical assessment of several DDR markers was performed on a collection of 21 pHGG diagnostic samples and 9 paired relapses. To validate the DDR functional inhibition, we used 3 patient-derived cell lines bearing H3.3K27M mutations. A finalized signature of 28 genes involved in DNA repair and cell cycle machineries was used to cluster in two groups the pHGG cohorts. The differential protein expression of PARP1, XRCC1, p53 and stem cell markers was linked significantly to the more resistant pHGGs and the rapid progressions after radiotherapy. Those DDR makers might be used as theranostic and therapeutic targets, which were screened in PDCLs with promising results.